MIGRATION AND CULTURAL IDENTITY: THE PROBLEM OF FINDING BALANCE (TAMADDUN NURI JURNALI, 2025)
This article provides a comprehensive analysis of the impact of global population migration on ideological processes. Migration flows can change the cultural, religious and political landscape of host societies, shape new trends and provoke social conflicts. The study examines the impact of migration on population identity, national values, political stability and social integration. Based on the results obtained, practical recommendations are given to policymakers on how to effectively manage migration processes and preserve cultural diversity.